KONTROL STRUKTUR GEOLOGI TERHADAP SEBARAN BATUBARA DI DAERAH MENUKUNG-NANGAPINOH KALIMANTAN BARAT - -, Iyan Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
Coal outcrop in Menukung area and Nangapinoh met in Melawi basin. This basin have experienced of several tectonic causes coal seam folded and faulted.Result of measurement entire coal outcrop shown strike between N 240°E – N 315°E with dip between 5° until 10°. Based on contruction result strike pattern known distribution coal in surface with orientation Southwest-Northeast and dip orientation Northwest, North until Northeast.dengan demikian sebaran batubara controlled by homocline fold structure. Based on strike and dip data and kind of geology structure that controlling it, so that known in northern research area have potention good enough.